Developing a Process for Deploying Systemic Countermeasures at Unsignalized Intersections: Case Study of Virginia. Issue 9 (September 2019) - Cottrell, Benjamin H.; Lim, In-Kyu
This paper discusses the process used to develop a safety improvement plan for unsignalized intersections using systemic low-cost countermeasures. The scope of this project focused on unsignalized intersections with stop sign control on the minor approaches. The first objective was to perform an assessment of Virginia's unsignalized intersection crashes over a five-year period to determine predominant crash trends and collision types to target for treatment. The four focus collision types with the highest frequency of crashes and the greatest potential reduction in crashes were 3-leg angle, 3-leg fixed object off the road, 4-leg angle and 4-leg rear end. Chi-square automatic interaction detection decision tree analysis was used to perform a systemic analysis to identify a group of intersections associated with potential risk factors related to the focus collision types. A tiered list of systemic countermeasures to deploy was developed. The countermeasures were intended to warn of the stop ahead, make the stop sign and stop location more visible on a minor street, and to warn of the intersection ahead on a major street. The potential for safety improvement measure was used to prioritize the candidate treatment intersections. Before deployment, a study of the intersection by district traffic engineering staff was planned to finalize the plan. The output from the research was a safety improvement plan to systemically deploy treatments to unsignalized intersections as part of the safety program.